Skin conditions of ruminant animals - Abdul Rahman, Sheikh Omar; Sze, E. K. (Malaysian Society of Applied Biology, 1984)
A total of 207 dairy cattle, 298 beef cattle, 126 buffaloes. 210 goats and 108 sheep in UPM farms were examined for skin conditions. Dairy and beef cattle had high prevalence of tick infestation. The Bos indicus breeds were less severely affected than the Bos taurus breeds and BoopbiIus microplus and Haemaphysalis bisplnosa were the principle ticks Identified. Bovine papillomatosis was common in both herds but were of low prevalence. Lice infestation with Damalinia caprae was found in loats under both intensive and semi-intensive fanning system. Mange was a problem in the intensive system of goat farming but not in the semi-intensive system. Chorioptes caprae was the main causal agent followed by Psoroptes cuniculli, There was a total absence of ectoparasitism in the kids. Contagious ecthyma was observed at low prevalence in goats.